The Kalachuris and Their Architectural Legacy in Dakshin Kosala - Tiwari, Dr. Anju (Integrated Journal for Research in Arts and Humanities, 2024)
The Kalachuri dynasty, a crucial force in the history of Central India, is best understood through the rise of its three major branches: Mahishmati, Tripuri, and Ratanpur. The latter, the Ratanpur Kalachuris, initially based in Tummana (modern-day Korba District, Chhattisgarh) before relocating to Ratanpur (Bilaspur District, Chhattisgarh), played a vital role in shaping the cultural, religious, and architectural heritage of Dakshin Kosala. Although the Ratanpur Kalachuris were initially subordinate to the Tripuri Kalachuris, their reign flourished under the leadership of King Jajalladeva I during the early 12th century, marking the zenith of their political and cultural influence. This dynasty continued its rule until Pratapamalla (1188–1217 AD), with an interlude before the division of the Kalachuri state into two branches: Ratanpur and Raipur, in the 15th century. Central to their legacy is a rich architectural heritage, particularly evident in the temples, forts, and water reservoirs that dot Dakshin Kosala. These structures embody a fusion of regional and cultural elements, showcasing the Kalachuris' support for Shaktism, their promotion of local artistic traditions, and their influence on religious practices. The Mahamaya Temple in Ratanpur, dedicated to the family deity of the Kalachuris, exemplifies this synthesis and remains a key cultural and religious symbol in the region. The architectural output of the Kalachuris is more than just a testament to their religious devotion; it provides invaluable insights into the religious and cultural life of Dakshin Kosala and continues to influence local practices today.